2009
DOI: 10.1029/2008gl036162
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of Labrador Sea Water in 2008

Abstract: A May 2008 oceanographic survey of the Labrador Sea and recent Argo float profiles have revealed that convective overturning extended to a depth of about 1600 m during the winter of 2008, resulting in the production of a large “year class” of Labrador Sea Water. This convection was the deepest since 1994, and substantially exceeded the convection to 500–1100 m in the past few years in both the Labrador and Irminger Seas. The resultant 0.2°C cooling of the intermediate‐depth waters in the Labrador Sea has disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
189
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(214 citation statements)
references
References 9 publications
23
189
0
2
Order By: Relevance
“…In 2000 an LSW class, LSW 2000 , was formed in a single winter. In the winter of 2008 a similar formation of a singlewinter LSW class could be observed (Våge et al, 2009;Yashayaev and Loder, 2009). The LSW classes differed in density and other hydrographic characteristics, depending on their formation history.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…In 2000 an LSW class, LSW 2000 , was formed in a single winter. In the winter of 2008 a similar formation of a singlewinter LSW class could be observed (Våge et al, 2009;Yashayaev and Loder, 2009). The LSW classes differed in density and other hydrographic characteristics, depending on their formation history.…”
Section: Introductionmentioning
confidence: 68%
“…Therefore these data are not fit for the study of local formation process of LSW in the Irminger Sea as proposed by Pickart et al (2003), Bacon et al, (2003), and Falina et al (2007), nor for the study of the upper LSW, formed in the Labrador Sea by shallow convection near the boundary currents (Kieke et al 2006;Rhein et al, 2007). Våge et al (2009) and Yashayaev and Loder (2009) have shown that profiling floats make a view of the deep convection process possible that cannot be achieved by the use of our or similar data sets. However, sufficient amounts of profiling float data in our research area are only available for the last 13 years (Centurion and Gould, 2004;Yashayaev and Loder, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a series of cold winters could replace these water masses with the newly ventilated LSW containing high concentrations of anthropogenic CO 2 . Consequently, the saturation horizon in the Labrador Sea will not shallow gradually, but it will be controlled by intermittent deeper convections, such as those observed in early 1990s, 2000, and 2008 [Våge et al, 2009, Yashayaev andLoder, 2009].…”
Section: The Labrador Seamentioning
confidence: 99%
“…Subsequently, in the North Atlantic, the absence of deep convection in the sub-polar gyre for over a decade from the mid-1990s to mid-2000s raised concerns that ocean circulation was already being affected by climate warming. However, there was an abrupt resumption of deep convection in the Labrador and Irminger Seas in winter (Vage et al 2009Yashayaev and Loder 2009).…”
Section: Ocean Circulationmentioning
confidence: 99%